Detection of Integrase Gene in E. coli Isolated from Pigs at Different Stages of Production System - Eulalia de la Torre; Rocío Colello; Nora Lía Padola; Analía Etcheverría; Edgardo Rodríguez; Fabián Amanto; María Ofelia Tapia; Alejandro Luis Soraci (International Journal of Microbiology)
Integrons are one of the genetic elements involved in the acquisition of antibiotic resistance. The aim of the present research is to investigate the presence of integrons in commensal Escherichia coli (E. coli) strains, isolated from pigs at different stages of production system and from the environment in an Argentinian farm. Five sows postpartum and five randomly chosen piglets from each litter were sampled by rectal swabs. They were sampled again at day 21 and at day 70. Environmental samples from the farm were also obtained. E. coli containing any integron class or combination of both integrons was detected by polymerase chain reaction in 100% of sows and in piglets at different stages of production: farrowing pen stage 68.1%;, weaning 60%, and growing/finishing 85.8%, showing an increase along the production system. From environmental samples 78.4% of E. coli containing any integron class was detected. We conclude that animals and farm environment can act as reservoirs for potential spread of resistant bacteria by means of mobile genetic elements as integrons, which has a major impact on production of food animals and that can reach man through the food chain, constituting a problem for public health.